Role of acidic fluids in Earth’s deep lithosphere: Insights from the Neoarchean magmatic roots of the Nilgiri Block, southern India - Samuel, Vinod O.; Santosh, M.; Jang, Yirang; Kwon, Sanghoon (Frontiers in Earth Science, 2022)
Fluids play a major role in facilitating igneous/metamorphic processes in the Earth’s crust and mantle. In this study, we investigate the nature and composition of fluids in Earth’s interior by studying the lower crustal rocks. We compare accessory minerals (e.g. apatite, monazite, allanite and titanite), their texture, mineral reactions and composition among regionally distributed metamorphosed mafic and felsic rocks representing the roots of Neoarchean arc magmatism from the Nilgiri Block of the Southern Granulite Terrane in India. Regional trends in accessory minerals show the formation of monazite, allanite and titanite in the felsic rocks. Apatite is depleted in REEs in all the rock types, irrespective of the difference in their whole-rock chemistry. Textural features and mineral reactions show that these accessory minerals were affected by fluids present in the lower crustal conditions. By comparing our results with those from previous experimental results, we further show that acidic CO2-H2O-HCl-HF fluids stable in lower crustal conditions could have resulted in these chemical and textural features. Dielectric constant of water is high (10–35 compared to lower crustal conditions) in high-pressure and low-temperature conditions of subduction zones and the upper mantle. Such conditions would enhance dissociation of HCl (compared to lower crust) and result in acidic fluids during dehydration reactions in subduction zones and in the upper mantle. Our results have important implications in understanding the nature and composition of fluids in Earth’s interior and would be helpful to model the tectonic and deep geochemical processes in both early and modern conditions in planetary interiors.